DISKUSI BERBASIS VIRTUAL RESEARCH PADA PERKULIAHAN IPBA - Supriyadi, Supriyadi; Rusilowati, Ani (Jurnal Penelitian Pendidikan, 2011)
Background of the research is experience in teaching IPBA (Science of Earth and Space) for some years. It shows that most of students’ final test results are not satisfied. It is caused by some factors, such as low student’s motivation, less learning source, featureless and monotonous teaching method (lecturercentred). For solving the problem, discussion is applied in teaching with the teaching material from related virtual research. The objectives are (1) giving experiences to students for doing research by using virtual research, (2) giving ability for writing research result in the form of paper ksmethod are (1) introduction, (2) determining research topic for each group, (3) doing research, (4) discussion, (5) evaluation. The research result shows that students’ understanding about research material presentation is good. It is showed in discussion, questions in discussion is difficult and must be answered by combining one concept and other concepts. The change of giving questions and responds is used well by participants. In every discussion material there are about 12 students give high quality questions and responds. The questions and responds can be answered well by group that presents material.